Properties of multicomponent (Mn-Ni-Co-Al-Si-Ti) oxide spinel hierarchically organized nanostructures deposited by magnetron sputtering in two temperatures. - Sagan, P.; Frugynskyi, M.; Mroczka, R.; Wisz, G. (Physics and Chemistry of Solid State, 2021)
Multicomponent spinel films were deposited on Ag/Si substrates by magnetron sputtering. Two substrate temperatures were used. XRD diffraction measurements show that the layers are composed of three metals oxides (Mn2O3, NiO, CoO). The presence of spinel phase is poorly visible. However, electron diffraction measurements (RHEED) clearly confirmed the presence of nanostructured spinel structure on top of the samples. Moreover, AFM measurements show that nanostructured spinel islands are present on the sample surface. The measurements validated that indeed, hierarchically organized spinel-oxides nanostructures were obtained. A possible model growth of the spinel nanostructures at different temperatures is discussed.